2014
DOI: 10.3389/fimmu.2014.00289
|View full text |Cite
|
Sign up to set email alerts
|

Which Antibody Functions are Important for an HIV Vaccine?

Abstract: HIV antibody (Ab) functions capable of preventing mucosal cell-free or cell-to-cell HIV transmission are critical for the development of effective prophylactic and therapeutic vaccines. In addition to CD4+ T cells, other potential HIV-target cell types including antigen-presenting cells (APCs) (dendritic cells, macrophages) residing at mucosal sites are infected. Moreover, the interactions between APCs and HIV lead to HIV cell-to-cell transmission. Recently discovered broadly neutralizing antibodies (NAbs) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 188 publications
(212 reference statements)
2
51
0
Order By: Relevance
“…[1][2][3] While the interest in NAb is clear, it should be stressed that RV144 was the only vaccine efficacy trial showing protection against HIV acquisition with little NAb activity but with new patterns of non-NAbs that may block transmission. [4][5][6] Similarly, V2 antibodies seem important for protection against SIV and SHIV challenges. 7 Although this study did not measure non-NAbs, in particular V1 and V2 identified as inversely correlated with risk of acquisition in RV144, this issue should be noted as deserving further studies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] While the interest in NAb is clear, it should be stressed that RV144 was the only vaccine efficacy trial showing protection against HIV acquisition with little NAb activity but with new patterns of non-NAbs that may block transmission. [4][5][6] Similarly, V2 antibodies seem important for protection against SIV and SHIV challenges. 7 Although this study did not measure non-NAbs, in particular V1 and V2 identified as inversely correlated with risk of acquisition in RV144, this issue should be noted as deserving further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Their contribution to protection may result from a variety of antiviral mechanisms, including direct neutralization of virus and Fc receptor-dependent effector functions such as antibody-dependent cell-mediated cytotoxicity (ADCC) or antibody-mediated phagocytosis (1)(2)(3)(4). Antibodies that directly neutralize HIV can provide protection, as evidenced in several nonhuman primate studies with passively transferred monoclonal antibodies (MAbs) (5)(6)(7)(8), although their role in preventing natural HIV transmission remains equivocal (reviewed in reference 9).…”
Section: Hiv/aidsmentioning
confidence: 99%
“…59 Therefore, though only weakly neutralizing, Ab induced by RV144 may potentially mediate protection through aggregating or immobilizing virions in mucin layers, impeding transverse through mucosal barriers, [60][61][62] via IgG Fcg receptor (FcgR) dependent ADCVI including ADCC, [55][56][57] ADCP, 56,57 Ab-mediated release of cytokines or chemokines and complement-mediated killing. [50][51][52]59,63,64 ( Fig. 1).…”
Section: Rv144mentioning
confidence: 99%